Pengaruh Corona Virus Disease 2019 (Covid-19) Terhadap Tren Indek Saham Sektoral: Pengaruh Corona Virus Disease 2019 (Covid-19) Terhadap Tren Indek Saham Sektoral - Dwi Ayu Lusia; Darmanto Darmanto (Litbang PWM Jawa Tengah, 2020)
The spread of Covid-19 since April 2020 has had a high number of cases and / or number of deaths and this can spread to various regions and countries. So that the Indonesian government issued a large-scale social restriction regulation. This will have an impact on sectoral aspects in Indonesia. Therefore this study was made with the aim of knowing the effect of Covid-19 on the sectoral stock index trend and how it affects them. The data used are monthly data on sectoral stock index prices (11 sectors) from January 2010 to March 2020 (before covid-19) and April to October 2020 (ongoing covid-19). Based on a comparison between the regression coefficients before and the onset of Covid-19, it can be seen that the sectors not affected by Covid-19 are basic industry, consumer industry, development, finance, manufacturing, other industries, property and trade. The absence of covid-19 influence on the sector is evidenced by the existence of a slice between the regression coefficients between before and during covid-19. The agriculture, infrastructure and mining sectors were affected by Covid-19. The infrastructure sector has experienced a trend change from rising to being stagnant. Meanwhile, the agricultural and mining sectors experienced a trend change from down to up.